Pengaruh Pendekatan Pembelajaran dan Gaya Berpikir terhadap Hasil Belajar Keterampilan Elektronika setelah Mengontrol Pengetahuan Awal - Zulrahmat Togala (JTP - Jurnal Teknologi Pendidikan, 2015)
This study aims was to determine the effect of learning approach and thinking style towards learning outcomes of electronics skills, after controlling prior knowledge. The participants were 36 students were divided into two treatment classes. Data analysis was Analysis of Covariat (ANCOVA). Results of the study: (1) scientific approach capable of providing a better impact for improvement of learning electronics skills than expository approach; (2) there was an interaction effect between learning approach and thinking style towards learning outcomes electronics skill after controlling prior knowledge; (3) students who have a more precise of divergent thinking is taught with scientific approach after controlling prior knowledge; (4) expository learning approach more effective for students who have convergent thinking after controlling prior knowledge